Role of E2-Ub-conjugating enzymes during skeletal muscle atrophy - Polge, Cecile; Attaix, Didier; Taillandier, Daniel (Frontiers in Physiology, 2015)
The Ubiquitin Proteasome System (UPS) is a major actor of muscle wasting during various physio-pathological situations. In the past 15 years, increasing amounts of data have depicted a picture, although incomplete, of the mechanisms implicated in myofibrillar protein degradation, from the discovery of muscle-specific E3 ligases to the identification of the signaling pathways involved. The targeting specificity of the UPS relies on the capacity of the system to first recognize and then label the proteins to be degraded with a poly-ubiquitin (Ub) chain. It is fairly assumed that the recognition of the substrate is accomplished by the numerous E3 ligases present in mammalian cells. However, most E3s do not possess any catalytic activity and E2 enzymes may be more than simple Ub-providers for E3s since they are probably important actors in the ubiquitination machinery. Surprisingly, most authors have tried to characterize E3 substrates, but the exact role of E2s in muscle protein degradation is largely unknown. A very limited number of the 35 E2s described in humans have been studied in muscle protein breakdown experiments and the vast majority of studies were only descriptive. We review here the role of E2 enzymes in skeletal muscle and the difficulties linked to their study and provide future directions for the identification of muscle E2s responsible for the ubiquitination of contractile proteins.